2014
DOI: 10.3892/ijo.2014.2666
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of deep sea water against doxorubicin-induced cardiotoxicity in H9c2 cardiac muscle cells

Abstract: Doxorubicin (DOX) is one of the most effective chemotherapeutic agents in the treatment of a variety of tumors. However, its clinical use has been compromised by the risk of cardiotoxicity. Thus, many efforts have been focused on exploring new strategies to prevent or reverse DOX-induced cardiotoxicity. Recently, deep sea water (DSW) has drawn much scientific interest for therapeutic intervention due to its enrichment in nutrients and minerals. In this study, we investigated whether DSW has protective effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…DOX is an anthracycline antibiotic and broad spectrum anti-cancer agent [6,7]. Although DOX is useful for the treatment of triple-negative breast cancer (TNBC), in practice its use is limited because of its serious side effects, which include cardiotoxicity, diarrhea, vomiting, hair loss, and nausea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOX is an anthracycline antibiotic and broad spectrum anti-cancer agent [6,7]. Although DOX is useful for the treatment of triple-negative breast cancer (TNBC), in practice its use is limited because of its serious side effects, which include cardiotoxicity, diarrhea, vomiting, hair loss, and nausea.…”
Section: Introductionmentioning
confidence: 99%
“…Although DOX is useful for the treatment of triple-negative breast cancer (TNBC), in practice its use is limited because of its serious side effects, which include cardiotoxicity, diarrhea, vomiting, hair loss, and nausea. Actually, the total dose of DOX administered must not exceed 450-500 mg/m 2 because of its cardiotoxicity [6]. Furthermore, reductions in DOX dosage made to address its side effects reduce its therapeutic efficacy [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of this valuable anticancer drug is limited by severe toxic side effects on the heart, which may result in heart failure (2). Numerous studies have implicated reactive oxygen species generation in the cardiotoxicity of DOX, which ultimately results in cardiomyocyte apoptosis (3,4). A number of pharmacological interventions have been proposed as therapies to oppose DOX-induced cardiotoxicity, including resveratrol (RES) and oleanolic acid (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, DSW has been shown to prevent atherosclerosis [ 20 ], attenuate the level of plasma lipid and adipogenic protein expression [ 21 ], and inhibit visceral fat accumulation and liver steatosis [ 22 ]. Furthermore, we previously demonstrated that DSW has anti-cancer metastatic [ 23 ], cardioprotective [ 24 ], and hypocholesterolemic effects [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%